PENGARUH BEBAN KERJA, PENGALAMAN AUDIT DAN TIPE KEPRIBADIAN TERHADAP SKEPTISME PROFESIONAL DAN KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN (Studi Empiris pada KAP di Kota Medan, Padang dan Pekanbaru) - Haura Faradina; Restu Agusti; Al Azhar L ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study was aimed to examine the direct effect of workload, audit experience, types of personality to professional skepticism and fraud detection ability of auditors, and also indirect effect of workload, audit experience, types of personality to fraud detection ability of auditors with professional skepticism as intervening variable. Collecting data of this study using a questionnaire submitted to 120 auditors who work at Accounting Public Office in Medan, Padang and Pekanbaru cities. Data analysis for hypothesis test was done with Partial Lease Square (PLS). Result of this study give evidence that workload and types of personality have significantly effect toward professional skepticism; didn’t find direct effect of audit experience toward professional skepticism; audit experience and professional skepticism have significantly effect toward fraud detection ability of auditors; didn’t find direct effect of workload and types of personality toward fraud detection ability of auditor; workload and types of personality have indirect effect toward fraud detection ability of auditors through professional skepticism. The value of adjusted R square for fraud detection ability of auditors and professional skepticism is 16,43% and 14,20%, which mean that workload, audit experience and types of personality can explain 16,43% and 14,20% of fraud detection ability of auditors and professional skepticism.Keywords: Workload, Audit Experience, Personality, Professional Skepticism and Fraud.